A study on clinical profile of typhoid fever at Government General Hospital, Nizamabad, Telangana, India - Singh, K. Gopal; Sundar, J. Syam (International Journal of Contemporary Pediatrics, 2019)
Background: The disease is most common in India. Children are most commonly affected. Typhoid fever, also known simply as typhoid, is a bacterial infection due to specific type of Salmonella that causes symptoms. Methods: Prospective observational study, 100 children with fever more than 7 days attending pediatric departed at GGH, Nizamabad were included in this study. Results: Total 100 children included in this study, male were 62, female were 38. More cases were (43) in 5-10 years age group, 53 children, belongs to middle class, 30 children belongs to lower class and 17 children belongs to upper class. Most common physical finding was toxic look (52), fallowed by coated tongue (41), hepatomegaly (32), pallor (12), spleenomegaly (11), hepatospleenomegaly (8). Conclusions: Safe drinking water, hand washing, proper sanitation, health education to children and food handlers in schools and hostels will decrease the incidence of typhoid fever in children.